Analysis of Consumer Assessment of Railway Service Performance in the New Normal Era and Before the New Normal - Yuzri Andrean; Bambang Riyanto; Mudjiastuti Handajani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Covid-19 is a pandemic throughout the world and is evidenced by regulations requiring masks, vaccinations, and PCR swabs related to personal protection to minimize Covid-19 infection. This condition has become the subject of discussion among many circles, one of which is the health protocol when carrying out activities outside the home, especially on public transportation. This triggered the emergence of vaccination programs and masks and PCR swabs in public transportation. In addition, public support for transportation is very high on the grounds of shortening travel time. The purpose of this research is the consumer's assessment of the performance of train services in the new normal era and before the new normal from the aspect of reusability, service quality and marketing mix. The method used is benchmarking by applying the principles of usability, service quality and marketing mix. The collection was carried out through a survey of 120 respondents who had used train services in the new normal era and before the new normal. The result of the research is that the train service before the new normal is superior in the eyes of consumers in terms of usability, service quality, and marketing mix. However, the new normal era trains have higher services than the new normal trains on the efficiency and error indicators in the usability aspect as well as on the tangible indicators in the quality aspect.